Strategi Guru Dalam Mengatasi Kesulitan Belajar Siswa Kelas X IIS Mata Pelajaran Geografi di MAN 4 Denanyar Jombang - Muhammad Zainul Arifin; Binti Maunah (CV Putra Publisher, 2023)
The aim of this research is to determine the learning difficulties experienced by students in the geography subject of class This research uses qualitative methods. This type of research uses qualitative research which aims to understand the object being studied in depth. Descriptive research carries out analysis only to the level of description, namely analyzing and presenting facts systematically so that they are easier to understand and draw conclusions from. The learning difficulties experienced by students are mainly difficulty understanding the material so the teacher provides a form of formative test evaluation in the form of a pre-test and post-test, apart from that the teacher also provides a contextual approach that connects the material with everyday life. The strategy used by teachers to overcome learning difficulties is the donkey bridge strategy using lecture, inquiry, discussion and snowball throwing methods. As a result, students can easily understand the material and easily differentiate the material and the teacher also gives a test question to determine the results of student learning using attitude and knowledge assessments.